ANALISIS YURIDIS TERHADAP PEMBUATAN AKTA PENDIRIAN CV TANPA ADANYA PERSERO KOMANDITER - CUT RAISHA YANNAZ (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Sunarmi3. Dedi Harianto In the establishment of CV as regulated in KUHD (Commercial Law Code), its organizer has to consist of a minimum of 2 (two) persons i.e. active and passive corporations;both corporations can monitor one to another in every activity it does. According to the result of the research, it is found out that the procedures of CV establishment deed issuance are started from an agreement among parties to establish a CV; they all come before a notary by taking their ID cards with them and providing information of the CV. The CV establishment deed is registered to the Registrar of the local District Court in the CV domicile in the Registrar Room. The requirements are the NPWP CV (the tax ID number of the CV). Copies of ID Cards, copies of the CV establishment deed and the Letter notifying the domicile of the CV. After the registration is done, the establishment of the CV is announced in the Additional News of The Republic of Indonesia. CV (Limited Partnership) manages the activities which are daily routines, nota daily routines, not routine but are new or special. The establishment contract of CV.A does not meet the objective requirement of its legality; the legitimate reasons and its juridical results is that the contract is annulled before the law.Keywords : Deed, Limited Partnership, Legal Force.